The Effect of Osteogenic Induction Medium on Mineralization between Human Jaw Periosteum Cells and Dental Pulp Cells - Jantapalaboon, Danupon; Kaewsuwan, Kanruethai; Yortchan, Witsanu; Choorujiporn, Parichat; Puwanun, Sasima (Naresuan University Journal: Science and Technology (NUJST); Vol 26 No 1 (2018): January - March 2018, 2018)
The most common birth defect in craniofacial area is a cleft defect with an incidence of 1.7:1000 live births. The current treatments involve many steps of surgical procedures and cause morbidity at the donor site when harvesting bone for filling the gap defect. It may be possible to treat cleft palate defects by bone regeneration strategies using osteoprogenitor cells to form the hard tissue. The aims of this project are to select a suitable cell source between human jaw periosteum (HJPs) and dental pulp cells (DPCs) for repairing the bone part of a cleft palate.      Donor who attended a wisdom tooth surgical removal was collected both HJPs and DPCs for the same time at Dental Hospital, Naresuan University. In this study, 3 donors were used with ethical approved by Human research committees, Naresuan University. Both HJPs and DPCs were isolated and cultured in the osteogenic induction medium which supplemented with Dexamethasone (Dex). A cell proliferation was measured by using Hoechst 33258. An osteogenic differentiation potential was measured by alkaline phosphatase (ALP) activity on day 7, 14, 21, and 28 days and calcium mineralization by using alizarin red staining on day 28.      The HJPs and DPCs showed increased in the cell proliferation overtime for 28 days of culture with no difference between cell types. HJPs showed the osteogenic potential by increasing ALP activity over 21 days and decreasing on day 28 of experiment. However, DPCs showed an increasing ALP activity over 14 days and then decreasing on day 21 and 28. The calcium mineralization on monolayer culture showed no difference between HJPs and DPCs.      Both HJPs and DPCs have the osteogenic potential under Dex supplementation. Bone regeneration strategies by using both HJPs and DPCs could benefit in cleft palate treatment compared to the current treatments (autologous bone graft from iliac crest) to promote bone formation at the defect area and enhance development of facial structure in the future.
Keywords: Cleft palate, bone tissue engineering, osteoprogenitor cells